Cabaran-Cabaran Pengajian Usuluddin & Falsafah di Alaf Baru - Dakir, Jawiah; Ibrahim, Mazlan; Awang, Jaffary; Mohamed, Ibrahim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
The department of Usuluddin and Philosophy (JUF) of Faculty of Islamic Studies, National University of Malaysia was established since 30 years ago. Since then, the department had undergone development in various aspects. In terms of student member, it has remarkably increased since 1999/2001 session when student of the faculty were given freedom to choose their own department. Coursewise, however, philosophy-based courses offered by the department failed to attract students. This study tries to find out the reasons behind this phenomenon.